The Economic Burden and Non-Adherence Tuberculosis Treatment in Indonesia: Systematic Review - Diniawati, E; Wibowo, A (KnE Life Sciences, 2019)
Until today, Tuberculosis (TB) is still taking part as a world health problem, especially in The South East Asia Region. TB in South East Asia contributes almost 50% of the worldwide burden. Indonesia is one of the regional countries that provide to the statistics, and the World Health Organization (WHO) enlisted it in the 30 High-TBBurden Countries. The high number of TB in Indonesia mostly caused by a lack of case registration, non-adherence of treatment, and lost to follow-up. This study conducted an overview of systematic review based on Prisma Protocol to systematically and objectively focus on the economic burden as a risk factor of non-adherence of TB treatment in Indonesia. Relevant literature was searched from PubMed, Science Direct, Google Scholar and reviewed abstracts and full-text article based on eligibility criteria. Seven studies included in this review after selected using inclusion and exclusion criteria. The studies revealed a consistent association between economic burden as a risk factor of non-adherence of TB treatment. In conclusion, financial burden was significant with non-adherence of TB treatment and most of TB patient who stopped the treatment should spare their family spending into TB treatment and this often constitutes to more considerable financial risk for them. Keywords: Tuberculosis, Economic burden, Non-adherence, Indonesia